Design and characterization of a fractal-inspired multi-frequency piezoelectric energy converter - Davide Castagnetti (Fracture and Structural Integrity)
A promising harvesting technique, in terms of simplicity and efficiency, is the conversion of ambient kinetic energy through piezoelectric materials. This work aims to design and investigate a piezoelectric converter conform to a fractal-inspired, multi-frequency structure previously presented by the author. A physical prototype of the converter is built and experimentally examined, up to 120 Hz, in terms of modal response and power output. Three eigenfrequencies are registered and the power output is particularly good at the fundamental eigenfrequency. Also the effect of the resistive load applied to the converter is investigated.